Social housing in Portugal and Italy: methodological issues and empirical inferences of a comparative study - Di Giovanni, Caterina Francesca (2019)
This working paper aims to clarify some aspects of social housing in Portugal and Italy in order to start a comparative analysis of the interventions in social housing neighbourhood’s case studies in the two countries. Divided into three parts, the paper initially discloses an explanation of methodological issues for a housing comparative study, especially for the Southern Europe countries, continuing with the description of housing concepts used in Portugal and Italy and concluding with a preliminary comparison. Despite having the same percentage of social housing, Portugal and Italy are different in the way how to deal with it and this research longs to explain it. The study offers methodological directions on how to conduct a housing comparative research and displays a starting comparison on statistical data, political genealogies, normative concepts and historical frameworks. The purpose is to settle a theoretical basis and reveal some outcomes from the analysis of the social housing in the two countries. This work seeks to contribute to the general debate of comparative housing studies of Southern Europe.